Isolated mild fetal ventriculomegaly. Report of a case - Monzón Castillo, Elí Pedro (2023)
Ventriculomegaly is a marker of abnormal brain development and is a cause forconcern when present. It has a prevalence of 0.3-1/1000 live births and is morefrequent in male fetuses. Ventriculomegaly is defined as the atrioventriculardiameter of the lateral ventricles greater than or equal to 10 mm. A measurementof 10-15 mm constitutes mild ventriculomegaly while values >15 mm constitutesevere ventriculomegaly. Ventriculomegaly may be isolated or associated with otheranomalies including abnormal structural findings, chromosomal abnormalitiesor prenatal infections in about 50-84% of cases. If ventriculomegaly is mild andisolated, the most frequent outcome is normal. Survival of newborns with isolatedmild ventriculomegaly is high, with reports of 93-98%. The probability of normalneurodevelopment is greater than 90% and will not be different from that of thegeneral population. Therefore, in the presence of isolated mild ventriculomegaly, aftera complete evaluation, the pregnant woman should be informed that the prognosisis favorable, and that the child will probably be considered normal. We present acase of isolated mild left ventriculomegaly detected in the prenatal ultrasound at20 weeks, who underwent serial neurosonographic controls, genetic amniocentesisand study of prenatal infections, the latter two being normal and showing resolutionof ventriculomegaly, as well as postpartum control within the limits of normality.